Augmented Reality-Based Laptop Digital Catalog Application - Shiddqy Hidayat, Syahril; Taurusta, Cindy; Eviyanti, Ade; Senja Fitrani, Arif (Research Parks Publishers, 2025)
Augmented Reality is a system that supports the real world with virtual (computer-generated) objects that appear together in the same space/place as the real world. One of the uses of Augmented Reality is as a promotional medium. The application of Augmented Reality (AR) in promotional media aims to increase the interest of consumers who are not satisfied with conventional promotional media. With conventional media, the attractiveness of an item is still not maximized. Based on the results of the research and the application made, it can be concluded that the